1992
DOI: 10.1136/bmj.305.6860.989
|View full text |Cite
|
Sign up to set email alerts
|

Avian exposure and bronchogenic carcinoma.

Abstract: 2 Carstensen JM, Axelson 0. Changes in non-smoking related lung cancer with special reference to mortality trends in Swedish wvomen. In: Davis DI_. Hocl DG, eds. 7rendts tii catcer sInrtalitv ill industritl coubtni's. New York: New

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 1 publication
2
12
0
Order By: Relevance
“…The finding by Holst et al [22] of a highly significant increased risk of lung cancer in households in which cer tain types of bird, particularly canaries and budgerigars (parakeets), are kept as indoor pets, and the confirmation of this finding by other investigators [23,24], is clearly something which should not be ignored. Knowing that the keeping of pet birds in the house is a source of antigens which can give rise to asthma in atopic persons, one won ders whether other sources of antigens e.g.…”
Section: Upper Respiratory Infectionssupporting
confidence: 49%
“…The finding by Holst et al [22] of a highly significant increased risk of lung cancer in households in which cer tain types of bird, particularly canaries and budgerigars (parakeets), are kept as indoor pets, and the confirmation of this finding by other investigators [23,24], is clearly something which should not be ignored. Knowing that the keeping of pet birds in the house is a source of antigens which can give rise to asthma in atopic persons, one won ders whether other sources of antigens e.g.…”
Section: Upper Respiratory Infectionssupporting
confidence: 49%
“…1 Although the relation between respiratory Chlamydia psittaci infection (avian exposure) and female lung cancer remains open, [2][3][4] C. pneumoniae infection has been repeatedly shown to be associated with lung cancer in male smokers as defined by serum cotinine. [5][6][7] We have now evaluated the association between past infection with C. pneumoniae and female lung cancer in a case-control study nested in a cohort of 650,000 fertile Finnish women established in 1983.…”
Section: Dear Sirmentioning
confidence: 99%
“…Five studies have examined whether keeping pet birds in the home is an independent risk factor for lung cancer (156)(157)(158)(159)(160). The earliest of these studies reported a 6.7-fold risk of lung cancer associated with bird keeping, after adjustment for smoking and vitamin C intake (156).…”
Section: Pet Birdsmentioning
confidence: 99%